Computer simulation of high-current ion bunches transport and acceleration with additional space charge compensation by thermal electrons - Manuilenko, O.V.; Karas, V.I. (Вопросы атомной науки и техники, 2014)
The particle in cell simulation results, within the limits of the complete set of the Maxwell-Vlasov equations, of the short (the ion bunch length is much smaller than the cusp length) and long (the ion bunch length is much longer than the cusp length) high-current compensated tubular ion bunches transportation and acceleration in the peaked fence magnetic field are presented. The ion bunch current, at injection in the cusp, is compensated by an accompanying electron bunch. Additional compensation of the ion bunch space charge by means of thermal electrons generated in the drift space has been studied. It is shown that both for short and for long ion bunches, the optimized additional space charge compensation by thermal electrons leads to a reduction of the energy spread of the accelerated ion beam at the output of the cusp.